1993
DOI: 10.1016/0022-0248(93)90850-v
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Hg1−xCdxTe single crystals by travelling heater method under accelerated crucible rotation conditions

Abstract: The accelerated crucible r9tation technique (ACRT) has been applied to the THM growth of Hg I _xCdxTe crystals to grow the crystals at a higher rate. These higher growth rates, which should be achieved by extending the regions of convectional stirring towards the interfaces, have been used in an attempt to explain the results in terms of simple constitutional supercooling arguments. Some different ACRT cycles which fulfil simple hydrodynamic and geometric criteria have been studied. The grown crystals were inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(15 citation statements)
references
References 15 publications
(28 reference statements)
0
15
0
Order By: Relevance
“…The growth of Hg 1Àx Cd x Te single crystals by THM using ACRT was proven to be possible by Bloedner and Gille [99]. They showed that the growth rate could be increased by extending the region of convective mixing toward the interfaces, as predicted by theoretical considerations.…”
Section: Accelerated Crucible Rotation Techniquementioning
confidence: 93%
See 1 more Smart Citation
“…The growth of Hg 1Àx Cd x Te single crystals by THM using ACRT was proven to be possible by Bloedner and Gille [99]. They showed that the growth rate could be increased by extending the region of convective mixing toward the interfaces, as predicted by theoretical considerations.…”
Section: Accelerated Crucible Rotation Techniquementioning
confidence: 93%
“…ACRT was initially modeled by Schulz-Dubois [175] and is discussed in detail in Chapter 24 of the Handbook, Vol. One can expect ACRT to be particularly efficient in the case of large diameters where the "supercooling amount" is quite large [99] and should impose excessively low growth rates. An improvement of the size of the crystals by a factor of 1000 over growth without ACRT was obtained by the authors.…”
Section: Accelerated Crucible Rotation Techniquementioning
confidence: 99%
“…Again, there is no marked difference from the results obtained by the vertical method. Slightly better uniformity achieved with vertical experiments [4,17] may be attributed to a higher stage of optimization reached in those techniques.…”
Section: Resultsmentioning
confidence: 99%
“…A smaller boundary layer thickness results in more stable growth conditions with respect to constitutional supercooling theory. In a recent paper on ACRT applied to vertical THM [17], we gave a simple explanation in terms of constitutional supercooling criterion arguments. The same approach is valid for THM growth with horizontal crucible rotation, as we believe the same situation applies adjacent to the growth interface as in ACRT.…”
Section: Theorymentioning
confidence: 99%
“…A significant improvement in both radial and axial compositional homogeneity was obtained. ACRT also allowed higher growth rates, up to 8.5 mm day −1 , to be obtained [21]. In another study this same group used horizontal rotation and compared the results with ACRT.…”
Section: Mass and Heat Transportmentioning
confidence: 99%